Penerapan Sanksi Terhadap Pelaku Residivis Penyalahgunaan Narkotika Di Lembaga Pemasyarakatan - Madaul, Riska; Supusepa, Reimon; Patty, Jetty Martje (Faculty of Law Universitas Pattimura, 2024)
ABSTRACT: Narcotics abuse is a crime and violation that threatens the safety, both physical and mental, of the user and also of the surrounding community socially. This narcotics abuse is not only carried out by narcotics abusers, but also by residents with prisoner status who are languishing in correctional institutions, thereby making prisoners entangled in the same cases. However, the deterrent effect of sanctions for this punishment is not considered to have a deterrent effect. In one of the narcotics cases committed by a drug recidivist, previously in 2018, the defendant with the initials MP was sentenced to 6 years in prison and languished behind iron bars. However, in 2021, precisely on January 17 2021, the defendant MP committed his crime again in a correctional institution. The aim of this research is to find out and analyze the application of sanctions against recidivist perpetrators of narcotics abuse in the Ambon Class IIA Correctional Institution and how efforts are made to control the circulation of narcotics in the Ambon Class IIA Correctional Institution. The research method used is empirical juridical research. The data sources used are primary data and secondary data. The technique for collecting legal materials is through interviews and then analyzed through descriptions using qualitative methods. The results of this research conclude that the application of sanctions to recidivists of criminal acts of narcotics abuse who distribute narcotics within prisons is by applying severe penalties to inmates as stated in Article 10 paragraph (3) of the Minister of Law and Human Rights Regulation Number 6 of 2013 regarding the Rules of Prisons and Detention Centers, which include being put in solitary confinement for 6 (six) days and can be extended for 2 (two) times 6 (six) days and not getting remission, leave to visit family, conditional leave, assimilation, leave before release, and parole within the current year and must be recorded in the guidance card, efforts to overcome the recidivism of criminal acts of narcotics abuse can be carried out through preventive and repressive efforts.